STRATEGIC GUIDELINES FOR DEVELOPING THE MONITORING OF HIGHER EDUCATIONAL INSTITUTIONS ACTIVITY AS A QUALITY ASSURANCE SYSTEM COMPONENT - Karamyshev, Dmytro (Pressing Problems of Public Administration, 2019)
The current transformations in the sphere of higher education under the conditions of the integration of Ukraine into the European and world community presuppose establishing new development guidelines for building an integral methodology for the strategic management of the higher education system and identifying the place of the leading higher educational institutions in this process.The objective of the research is substantiation of the essence, specific features of formation, organizational and legal basis for implementation, and strategic guidelines for development of the national system of rating of the results of higher educational institutions activity, based on the international practices of forming an integral methodology for monitoring educational activity, as a component of higher education quality assurance.The author emphasizes the need for forming an integral system of higher educational institutions rating aimed at a proper functioning, development and enhancement of the competitiveness of the domestic higher education system and its integration into the world systems of monitoring educational activity. It should be noted that achievements of higher educational institutions should be measured not only by absolute extensive indices describing the extent of their integratedness in the global systems and their resource capacity, but mainly by the criteria that evaluate the achievement of their strategic goal in terms of meeting social needs. The rating process must also take into account the efforts of the Ministry of Education and Science of Ukraine, being a central executive body in the sphere of regulating the development of the higher education system, directed to improve the above-stated system’s quality specifically for the domestic customers, who are users of educational services, with their further translating into competences which will be in demand, in the first place, in the domestic labor market.We deem it expedient, when performing the strategic planning and internal monitoring of higher educational institutions activity, to make allowance for specific evaluation criteria and use them to lay the foundation for building up a national system of higher educational institutions rating in Ukraine, as a component of an integral system for assessment of higher education quality.